Manajemen Perubahan Kepala Sekolah Menuju Sekolah Unggul di Sekolah Menengah Pertama - Arpinal, Arpinal; Jailani, M. Syahran; Musli, Musli (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article reveals the implementation of change management by the Principal towards a superior school at Ahmad Dahlan Junior High School, Jambi City. The main problem discussed is how is change management carried out by the Principal at the school? This article comes from descriptive qualitative research using data collection through observation, interviews and documentation. The research results show that school principals have played a key role in leading change towards superior schools by implementing important stages in change management, including; unfreeze stage, change stage, and refreeze stage. Obstacles that are often faced include; resistance from teachers, staff, students and parents as well as lack of resources and limited experience. Artikel ini mengungkap tentang penerapan manajemen perubahan Kepala Sekolah menuju sekolah unggul di Sekolah Menengah Pertama Ahmad Dahlan Kota Jambi. Permasalahan utama yang dibahas adalah bagaimana manajemen perubahan dijalankan oleh Kepala Sekolah di sekolah tersebut? Artikel ini berasal dari penelitian kualitatif deskriptif dengan pengumpulan data secara observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa kepala sekolah telah memainkan peran kunci dalam memimpin perubahan menuju sekolah unggul dengan melaksanakan tahapan-tahapan penting dalam manajemen perubahan antara lain; tahap unfreeze, tahap change, dan tahap refreeze. Kendala yang sering dihadapi antara lain; resistensi dari guru, staf, siswa dan wali murid serta kekurangan sumber daya dan keterbatasan pengalaman.